Liquid crystalline behaviour of self-assembled LAPONITE®/PLL–PEG nanocomposites. Issue 15 (19th February 2018) - Xu, P.; Lan, Y.; Xing, Z.; Eiser, E.
Abstract : By coating the flat faces of LAPONITE® disks with the comb-like polymer PLL–PEG we can fully suppress their aging in water and access their liquid-crystalline phases. Abstract : Synthetic LAPONITE®–clay particles with platelet-like shape display strong aging when dispersed in aqueous solutions, preventing the latter from reaching their natural liquid-crystalline equilibrium state. Here we introduce a facile method that successfully prevents this aging behaviour and enables accessing the systems' liquid-crystal and crystalline phases. We graft the comb-like polymer PLL–PEG (poly(l -lysine)- g -poly(ethylene glycol)) onto the clay surfaces from solution, thereby screening the negative surface charges and thus ensuring steric stabilisation. We show zeta-sizer and rheology measurements, respectively, confirming complete steric coating and that aging of dilute samples is completely suppressed even after a year. Using evaporation as a means to concentrate the particles, we observe various liquid crystalline textures under a polarized optical microscope (POM). Upon sequential spreading and drying, we are also able to obtain transparent films with hierarchical architecture.